1997
DOI: 10.1007/s000110050027
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tendon healing by nitric oxide

Abstract: Nitric oxide (NO) is a small, diffusible free radical that is generated from L-arginine by a family of enzymes, collectively termed the nitric oxide synthases. We investigated the role of NO in tendon healing. NO synthase activity and immunoreactivity was absent in un-injured rat Achilles tendon. After surgical division there was a five-fold increase in NO synthase activity and immunoreactivity within the healing tendon at day 7, with a return to near baseline levels at day 14. Inhibition of NO synthase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 16 publications
7
132
0
1
Order By: Relevance
“…11,12 Our previous reports also confirmed that NOS is upregulated during tendon healing and inhibition of NOS resulted in a significant reduction in cross-section area and failure load of healing Achilles tendon constructs. [13][14][15] We have also noted in our recent clinical trials, that application of topical nitric oxide improved early pain with activity, late functional measures, and outcomes of patients with extensor tendinosis, tendinosis of the extensor mechanism in the elbow, the Achilles and the supraspinatus in the shoulder. [16][17][18] Most of the findings, however, are from the studies on cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 78%
“…11,12 Our previous reports also confirmed that NOS is upregulated during tendon healing and inhibition of NOS resulted in a significant reduction in cross-section area and failure load of healing Achilles tendon constructs. [13][14][15] We have also noted in our recent clinical trials, that application of topical nitric oxide improved early pain with activity, late functional measures, and outcomes of patients with extensor tendinosis, tendinosis of the extensor mechanism in the elbow, the Achilles and the supraspinatus in the shoulder. [16][17][18] Most of the findings, however, are from the studies on cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 78%
“…48 The expression of growth factors and other potential modulators of tendon cell activity has been shown to increase in tendino pathy, including transforming growth factor β, platelet-derived growth factor receptor and neuro transmitters, such as glutamate and substance P. 42,47,[49][50][51] These changes might, however, be part of the healing response of the tissue and a requisite for tendon repair. 52,53 …”
Section: Molecular Pathology Of Tendinopathymentioning
confidence: 99%
“…5 We have shown that NO and the NOSs are important for the normal healing of rat Achilles tendon. 6 Transected Achilles tendons in rats in which NOS activity was inhibited [by means of oral administration of the NOS inhibitor N omeganitro-L-arginine methyl ester (L-NAME)] resulted in a significant reduction in cross-sectional area [30% at day 7 ( p < 0.01), and 50% at day 15 ( p < 0.001)] and failure load (24% at day 7, p < 0.01) of the healing tendon compared to untreated tendons. Rats fed L-NAMEs inactive enantiomer D-NAME healed normally.…”
Section: Introductionmentioning
confidence: 99%